The Influence of Economic Growth, Education and Unemployment on Poverty Rates in West Nusa Tenggara Province in 2017-2022 - Batari, Denita Dea; Siti Fatimah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
This study aims to analyze the effect of economic growth, education, and unemployment on the poverty rate in West Nusa Tenggara Province in 2017-2022 partially and simultaneously. The type of research used is descriptive quantitative research with the analysis technique used is panel data regression with E-Views 12 software. After testing the results obtained are partial economic growth has a negative and not significant effect on poverty levels, education has a negative and significant effect on poverty rate, and unemployment have a negative and not significant effect on the level of poverty. Meanwhile, simultaneously the three variables have a significant influence on the poverty rate in West Nusa Tenggara Province in 2017-2022.